Chronic Disease Management Program Exercise On Blood Pressure In Hypertensive Patients - Munir, Nur Wahyuni; Asfar, Akbar; Sakir, Rahmi; Asnaniar, Wa Ode Sri (Universitas Aisyah Pringsewu, 2021)
The management of hypertension can be done by using drugs or modifying lifestyle. Sports that are recommended for people with hypertension include gymnastics. One of the government programs is a form of aerobic physical exercise, namely chronic disease management program. The purpose of this study was to determine the effect of chronic disease management program exercise on blood pressure in hypertensive patients. This study used one group pretest posttest design which was conducted in May-July 2018 at the Batua Raya Makassar Health Center. Data collection using purposive sampling technique on 40 hypertensive patients using an observation sheet and mercury sphygmomanometer. Blood pressure measurements were taken once a week for four weeks. The statistical test used repeated ANOVA with a significance level of ? 0.05 and the result was p = 0.000. The results showed that most hypertensive patients who followed chronic disease management program exercise experienced a decrease in blood pressure. The conclusion of this study is there is an effect of chronic disease management program exercise on blood pressure in hypertensive patients. Hypertension patients are expected to be able to do chronic disease management program exercise regularly by following chronic disease management program exercise instructor to reduce blood pressure.